A Systematic Review on How Parental Involvement in ICT Enhances Digital Literacy and Language Learning - Putri, Regita Riani; Saharudin, Saharudin (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
Early childhood is a crucial period for developmental,where parental involvement and the integration of information and communication technology (ICT) significantly influence digital literacy and language learning.This study systematically reviews existing literatureto examine how parental engagement in ICT-based learning environments enhances children’s educational outcomes. Unlike previous research, this study provides a holistic analysis that integrated both digital literacy and language learning within early childhood education. The findings highlight that active parental participation not only fosters academic success and socio-emotional development but also mitigates some challenges associated with ICT use. While ICT enhances language acquisition and digital skills, concern such as cognitive strain, online safety risks, and disparities in internet access pose significant barriers to its effectiveness. This research underscores that necessity of structured parental involvement, equitable digital policies, and targeted ICT training for both educators and parents. Implementing these strategies can optimize children’s learning experiences and bridge existing gaps in digital literacy education, ensuring a more inclusive and effective integration of ICT in early childhood education.